Investigation of Point Merge Utilization Worldwide Using Opensky Network Data - Hardell, Henrik; Polishchuk, Tatiana; Smetanová, Lucie (Journal of Open Aviation Science, 2025)
Point Merge (PM) arrival procedures are currently in use at 44 airports across 20 countries worldwide. These procedures come in various design variants, including overlapping, partially overlapping, or separated sequencing legs. The positioning of sequencing legs within or outside of the Terminal Maneuvering Area (TMA) and the geometry of the arrival flows to PM or merging points impact the associated trade-offs between the PM system capacity and efficiency. In our study, we analyze the utilization of PM procedures at several airports implementing PM, using open-access ADS-B-based data from the Opensky Network. To identify flights that adhere to the PM procedures, we propose a catchment algorithm. The accuracy of the algorithm depends on the quality and completeness of the data, the specific design of the algorithm, and the complexity of the PM procedures. Generally, a well-designed catchment algorithm can achieve high accuracy by considering factors such as aircraft positions, speeds, and adherence to sequencing instructions. Then, we quantify PM utilization using performance indicators specifically tailored for this purpose. This paper builds upon previous research presented at the 11th OpenSky Symposium in 2023. We introduce an additional step to enhance the accuracy of the catchment algorithm and conduct a comprehensive sensitivity analysis of the catchment area size employed in the initial stage. We quantify the algorithm’s accuracy by considering false-positive and false-negative filtered trajectories. Furthermore, we compare the results of our proposed approach with the PM identification tool available in the Traffic Library.